An Ag-grid/graphene hybrid structure for large-scale, transparent, flexible heaters1. Issue 15 (21st April 2015) - Kang, Junmo; Jang, Yonghee; Kim, Youngsoo; Cho, Seung-Hyun; Suhr, Jonghwan; Hong, Byung Hee; Choi, Jae-Boong; Byun, Doyoung
<x xml:space="preserve">Abstract</x> We introduce highly transparent and flexible conductive films based on a hybrid structure of graphene and an Ag-grid.